EUROPEAN CONVENTIONS ON FAMILY LAW ISSUES: A VIEW FROM KAZAKHSTAN - Marat Aldangorovich Сарсембаев (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2022)
In this article the author analyzes the texts of a number of European conventions on certain matters of family law, formulates his proposals to improve the content of the rules of the conventions, conducts a comparative analysis of the norms of the European family law and related standards of the Kazakh family law.